Gray matter abnormalities in opioid-dependent patients: A neuroimaging meta-analysis. (3rd September 2017) - Wollman, Scott C.; Alhassoon, Omar M.; Hall, Matthew G.; Stern, Mark J.; Connors, Eric J.; Kimmel, Christine L.; Allen, Kenneth E.; Stephan, Rick A.; Radua, Joaquim
ABSTRACT: Background : Prior research utilizing whole-brain neuroimaging techniques has identified structural differences in gray matter in opioid-dependent individuals. However, the results have been inconsistent. Objectives : The current study meta-analytically examines the neuroimaging findings of studies published before 2016 comparing opioid-dependent individuals to drug-naïve controls. Method : Exhaustive search of five databases yielded 12 studies that met inclusion criteria. Anisotropic Effect-Size Seed-Based d Mapping ( A ES-SDM) was used to analyze the data extracted by three independent researchers. Voxel-based A ES-SDM distinguishes increases and decreases in brain matter significant at the whole-brain level. Results: A ES-SDM identified the fronto-temporal region, bilaterally, as being the primary site of gray matter deficits associated with opioid use. Moderator analysis revealed that length of opioid use was negatively associated with gray matter in the left cerebellar vermis and the right Rolandic operculum, including the insula. Meta-regression revealed no remaining significant areas of gray matter reductions, except in the precuneus, following longer abstinence from opioids. Conclusions : Opioid-dependent individuals had significantly less gray matter in several regions that play a key role in cognitive and affective processing. The findings provide evidence that opioid dependence may result in the breakdown of two distinct yet highly overlapping structural and functional systems. These are the fronto-cerebellar system that might be more responsible for impulsivity, compulsive behaviors, and affective disturbances and the fronto-insular system that might account more for the cognitive and decision-making impairments.